Improvement of the innovative functions in the administrative activity of the head of faculty - Perminova, A. (Problems of Engineer-Pedagogical Education, 2018)
The definition and classification of innovative functions of management is delivered in the article. An important condition for the effectiveness of control scientists believe the necessity for organic linkage control functions, both traditional and innovative, but the main principle of innovation in the management activities of the head of faculty should be innovative features, in which the objects of management should be involved not only students but also teachers of the faculty. It is found that management functions are activities that are clearly separated on the basis of the date of their Commission and management tasks. According to the task in the implementation of the management functions involved a significant number of members of the teaching team, and functions of the head are personal activities; the main criterion for determining the control functions is the matching of the types of management activities management steps; the main criterion for determining the functions of the chief educational institution is the correspondence of its activities to the current task. With the aim of improving management of the Department systematized and justified the necessity for the application of a body of innovative functions: predictive, managerial, legislative, political and diplomatic, consultative and developed the corresponding model. The developed model provides for the implementation stages (design, organizational, procedural, substantive, analytical and correctional) innovative features of administrative activity of the head of the Department, which creates the opportunity for systematic (deliberate, logical and consistent) applications in management. The improved model includes an analysis and detailed definition of the content of the duties of head of the Department in the implementation of the innovative functions of management.